1992
DOI: 10.1103/physrevlett.69.1845
|View full text |Cite
|
Sign up to set email alerts
|

Towards a singularity-proof scheme in numerical relativity

Abstract: Progress in numerical relativity has been hindered for 30 years because of the difficulties of avoiding spacetime singularities in numerical evolution. We propose a scheme which excises a region inside an apparent horizon containing the singularity. Two major ingredients of the scheme are the use of a horizon-locking coordinate and a finite differencing which respects the causal structure of the spacetime. Encouraging results of the scheme in the spherical collapse case are given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
221
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(225 citation statements)
references
References 8 publications
4
221
0
Order By: Relevance
“…It may also require the use of an "horizon excision" boundary condition (W. Unruh 1984, unpublished;Thornburg 1987;Seidel & Suen 1992). To simultaneously follow the extended disk may necessitate employing a nested grid or adaptive mesh refinement.…”
Section: Discussionmentioning
confidence: 99%
“…It may also require the use of an "horizon excision" boundary condition (W. Unruh 1984, unpublished;Thornburg 1987;Seidel & Suen 1992). To simultaneously follow the extended disk may necessitate employing a nested grid or adaptive mesh refinement.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper [18] we demonstrated that a horizon boundary condition can be realized. Here we present a more detailed discussion of our methods and various extensions to that earlier work.…”
Section: Introductionmentioning
confidence: 99%
“…This amounts to using a shift vector that locks the horizon in place near a particular coordinate location, and also keeps other coordinate lines from drifting towards the hole. In [18] we investigated one particular type of shift condition, namely the "distance freezing" shift. Here we report on various choices of shift conditions, including the original "distance freezing" shift that freezes the proper distance to the horizon, an "expansion freezing" shift that freezes the rate of expansion of outgoing null rays, an "area freezing" shift that freezes the area of radial shells, and the minimal distortion shift [19] that minimizes the global distortion in the 3-metric.…”
Section: Introductionmentioning
confidence: 99%
“…Current FD codes for evolving black hole spacetimes with excised horizons are mostly based on a numerical technique known as causal differencing [22][23][24][25][26][27], which allows one to update the fundamental variables in time while avoiding numerical problems associated with superluminal grid speeds. This technique has been used successfully to propagate an excised hole across a grid, even when grid points fall into or emerge from the horizon [25].…”
Section: Introductionmentioning
confidence: 99%